The Fundamentals of Monetary Fulfilment in Tax Administration - Popovič, Adrián (Public Governance, Administration and Finances Law Review, 2017)
In this article, the author discusses a brief definition of principles and fundamentals from a theoretical and legal point of view. Based on this division, the author characterizes and mentions principles and fundamentals that are applicable in a tax administration. The paper differentiates between the basic fundamentals of tax administration and the further fundamentals of tax administration. In this respect the author draws attention to the unnamed further fundamentals of tax administration which, until now, were not named by the theory of law. In the article the author mentions these fundamentals, analyses them and finds their application in tax administration. In particular, the author refers to the fundamentals of monetary fulfilment in tax administration, the definition of which can serve the better understanding of the nature of tax evasions and the improvement of the combat against them.